2009
DOI: 10.1007/s10461-009-9598-y
|View full text |Cite
|
Sign up to set email alerts
|

High HIV Prevalence Among Men Who have Sex with Men in Soweto, South Africa: Results from the Soweto Men’s Study

Abstract: The Soweto Men’s Study assessed HIV prevalence and associated risk factors among MSM in Soweto, South Africa. Using respondent driven sampling (RDS) recruitment methods, we recruited 378 MSM (including 15 seeds) over 30 weeks in 2008. All results were adjusted for RDS sampling design. Overall HIV prevalence was estimated at 13.2% (95% confidence interval 12.4–13.9%), with 33.9% among gay-identified men, 6.4% among bisexual-identified men, and 10.1% among straight-identified MSM. In multivariable analysis, HIV … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

26
216
7

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 221 publications
(249 citation statements)
references
References 23 publications
26
216
7
Order By: Relevance
“…The study is consistent with another study in South Africa that reported a higher number of male students more likely than females to consume more alcohol before engaging in sexual intercourse [21]. This study shows that there *Respondents who refrained from alcohol in the last 6 months were excluded from data analysis.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…The study is consistent with another study in South Africa that reported a higher number of male students more likely than females to consume more alcohol before engaging in sexual intercourse [21]. This study shows that there *Respondents who refrained from alcohol in the last 6 months were excluded from data analysis.…”
Section: Discussionsupporting
confidence: 90%
“…This can be attributed to sudden independence from parental monitoring students experience when they join university. In addition, literature review attributed the association between rural residence of students' childhood and inconsistent condom use to students'' sudden exposure to both active and liberal urban settings [11,20,21]. Previous studies also show that relocating to an urban university setting such as Durban city from rural upbringing such as Nongoma in KwaZuluNatal influenced their sexual behaviour [9,18].…”
Section: Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…Men who have sex with men (MSM) in Africa constitute a diverse group of men with different sexual identities and behaviours, many of which do not conform to a 'Westernised' gay identity (Lane, Mogale, Struthers, McIntyre & Kegeles 2008;Lane, Raymond, Dladla, Rasethe, Struthers & McFarland 2009). Many MSM identify as heterosexual and do not disclose their samesex behaviours.…”
Section: Background and Contextmentioning
confidence: 99%
“…[2][3][4][5] Until fairly recently, local and regional data were unavailable to inform targeted and appropriate health programming for this population group. South Africa's enabling constitution and government's (SAG's) commitment to providing appropriate care to key populations, including MSM, has provided an opportunity to gather data and develop and implement evidence-based health services.…”
mentioning
confidence: 99%